O.ABDIRAXMANOVTÍŃ SATIRALÍQ GÚRRIŃLERINDE KÓRKEM ShEBERLIK - Seytbekov, A.B. (SCIENCE and SOCIETY, 2026)
The article analyzes satire in Karakalpak literature and its theoretical foundations. The issue of satire in the short works and stories of the renowned orator O. Abdurahmonov has been discussed. The stories in the writer's collection of satirical stories “Qońsı-qobalar” were analyzed.